Use of magnesium sulfate in preterm deliveries for neuroprotection of the neonate. (January 2017) - Usman, Sana; Foo, Lin; Tay, Jasmine; Bennett, Phillip R; Lees, Christoph
Abstract : Key content: The prevalence of preterm birth is increasing and owing to advances in neonatal care, more infants are surviving. However, in parallel with this, the incidence of cerebral palsy (CP) is also rising. Magnesium sulfate (MgSO4 ) is currently recommended for use in women who are at risk of giving birth at less than 30–32 weeks of gestation for neuroprotection of their infants. The exact mechanism of action remains unclear. Meta‐analyses report encouraging results that are consistent with a modest but tangible benefit for the use of MgSO4, and suggest a number needed to treat (NNT) to prevent one in 46 cases of CP in infants born preterm before 30 weeks of gestation and one in 63 cases of CP in infants born preterm before 34 weeks of gestation. Learning objectives: To gain an understanding of the risk of neurodisability in infants delivered preterm. To become familiar with the main studies assessing the use of MgSO4 for neuroprotection in preterm deliveries. To become aware of the relevant international guidelines. Ethical issues: Concerns have been raised regarding the higher number of perinatal deaths reported with the use of MgSO4 in the MagNET study. This was not substantiated in the Cochrane review. Given that MgSO4 is a safe, readily available and inexpensive drug, even if there were only to be modest benefits from its use, the risk–benefit ratio is in favour of its use.